Preliminary Morphometric Analysis of Aethalops aequalis Populations in Sabah and Sarawak, Malaysian Borneo - R.C.T , Tingga; Abdullah, M.T (Chulalongkorn University, 2012)
Aethalops aequalis was previously recorded as a subspecies of A. alecto in Borneo. They are difficult to distinguish by external morphology as Malaysian Aethalops species are similar in size. The objective of this study was to characterize the morphological differences within the Malaysian A. aequalis populations based upon the evaluation of seven selected populations in Borneo. To this end, 11 skull and 11 dental characters were examined and analyzed using SPSS software. Six of these characters were found to be polymorphic across populations, with CM1 being the strongest character in most of the extracted functions followed by IM1, both of which are dental characters that relate to the lower jaw length. Character CM1 was generally shorter in most of the Southwest Sarawak populations compared to the Northeast Sarawak and Sabah populations. Aethalops aequalis from Sabah and Sarawak possessed a single skull morphotype and mountain isolation is, or has not yet been a sufficient barrier to lead to morphological divergence. The body and skull sizes were not affected by altitude or elevations, with A. aequalis possessing a single morphotype in Malaysian Borneo. In conclusion, little morphological variation was detected within and among the different geographical populations of A. aequalis in Sabah and Sarawak. The few differences found are likely to have arisen via natural selection driven adaptation to the new environment. KEY WORDS: Morphometric, Aethalops aequalis, Malaysian Borneo, skull, dental, single morphotype